A feasibility study on rainwater harvesting system for mosque in Perak Tengah / Muhammad Amirul Asraf Mohd Nordin and Nur Azfahani Ahmad - Mohd Nordin, Muhammad Amirul Asraf; Ahmad, Nur Azfahani (2018)
This feasibility study on Rainwater Harvesting System for the mosque in Perak Tengah is provided to make sure this system can give many benefits to the building users. From the feasibility study obtained on Rainwater Harvesting System (RWHS) for the selected mosque, it is found that RWHS has huge potential to reduce the building water bill every month. Since rainwater can be collected easily, it can be used directly for non-potable work such as landscape work, cleaning work and toilet flushing system. It can reduce the use of water from the main water supply. This research is obtained to support the development of green technology sector to align with the Government initiative towards the national green development. In this study, questionnaires have been distributed to the guest in the mosque. Besides that, interviews have been conducted with the management parties of the mosque organization. In addition, record of the water bill has been measured as a reference to this study. These approaches are important in order to investigate whether the RWHS is feasible to be installed in the mosque. The findings showed that Rainwater Harvesting System is suitable to be installed in the mosque in Perak Tengah. The system manage to save water, increase the usage efficiency and recycled the grey water for other water usage in the mosque.